2009
DOI: 10.1016/j.comcom.2008.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Network load-aware content distribution in overlay networks

Abstract: Abstract-Massive content distribution on overlay networks stresses both the server and the network resources because of the large volumes of data, relatively high bandwidth requirement, and many concurrent clients. While the server limitation can be circumvented by replicating the data at more nodes, the network limitation is far less easy to cope with, due to the difficulty in determining the cause and location of congestion and in provisioning extra resources. In this paper, we present novel schemes for mass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…It gives the maximum affordable number of subscribers and service channels. The issue of reducing link stress has also been considered in several other works ( [2], [13]). We found that content distribution sessions following our user grouping algorithm make a balanced use of the network bandwidth, which tends to cause the least interference to other users (See Section IV).…”
Section: B Network Load Metricsmentioning
confidence: 97%
See 2 more Smart Citations
“…It gives the maximum affordable number of subscribers and service channels. The issue of reducing link stress has also been considered in several other works ( [2], [13]). We found that content distribution sessions following our user grouping algorithm make a balanced use of the network bandwidth, which tends to cause the least interference to other users (See Section IV).…”
Section: B Network Load Metricsmentioning
confidence: 97%
“…The particular metrics we choose to capture the network load are known as the worst link stress (WLS) [2] and the degree of interference (DOI) [3].…”
Section: B Network Load Metricsmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards related works focused on architectures relying on overlays, reference [8] deals with selection strategies of clients by optimally partitioning them into disjoint subsets according to different criteria, such as network resource usage and the degree of congestion. Besides, optimal rate allocation in overlay-based CDN for efficient utilization of limited bandwidths has been investigated in [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Chul Han et al [61] try to assign the clients to appropriate servers, so that the network load is reduced and also well balanced, and the network resource consumption is low. This scheme allows scaling to very large systems because the algorithms are efficient and do not require network measurements nor topology or routing information.…”
Section: Content Distribution On Overlay Networkmentioning
confidence: 99%